2012
DOI: 10.1080/14786419.2010.545777
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of three medicinal Thai plants againstCampylobacter jejuniand other foodborne pathogens

Abstract: Leaves of Adenanthera pavonina, Moringa oleifera and Annona squamosa are used in traditional Thai medicine to treat dysentery and other diseases. This study investigated the antibacterial activity of these plants against six species of foodborne pathogen. Methods and solvents employed to extract active constituents were optimised using the disc diffusion assay. Phytochemical analysis of the optimised extracts was performed by thin layer chromatography (TLC). Minimum inhibitory concentrations (MICs) and minimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 32 publications
(30 reference statements)
1
16
0
Order By: Relevance
“…The crude extracts of Annona coriacea (species rich in aromatic acetogenins) have been observed to partially or totally disrupt midgut epithelial cells of A. aegypti [10]. However the use of crude extract does not indicate that the Annonaceae acetogenins cause these changes because plants of this family produce other secondary compounds toxic to insects, such as tannins, alkaloids and lectins [11]. …”
Section: Introductionmentioning
confidence: 99%
“…The crude extracts of Annona coriacea (species rich in aromatic acetogenins) have been observed to partially or totally disrupt midgut epithelial cells of A. aegypti [10]. However the use of crude extract does not indicate that the Annonaceae acetogenins cause these changes because plants of this family produce other secondary compounds toxic to insects, such as tannins, alkaloids and lectins [11]. …”
Section: Introductionmentioning
confidence: 99%
“…Zeid et al (2012) reported its use as a tonic. These reports of traditional use were most common in Asian countries (Wickramaratne et al, 2016;Koodalingam et al, 2015;Dholvitayakhun et al, 2012;Arshad et al, 2010).…”
Section: Ethnomedicinal Usementioning
confidence: 99%
“…A study carried out by Dholvitayakhun et al (2012) investigated the antibacterial activity of aqueous, ethanolic, and hexane extracts of leaves of A. pavonina against foodborne pathogens. Initially, the efficacy of extraction methods was assessed using the disc diffusion assay against Campylobacter jejuni, and erythromycin discs (10 μg/disc) were used as a reference.…”
Section: Antibacterial and Antifungal Activitiesmentioning
confidence: 99%
“…These phytochemicals are known to have many biological activities. In vitro studies show that Adenanthera pavonina leaf extract has antibacterial activity against the intestinal pathogen Campylobacter jejuni (Dholvitayakhun et al, 2012). Also, high doses of seed extract have an antiinflammatory effect in studies in rats and mice (Olajide, et al, 2004).…”
Section: Introductionmentioning
confidence: 99%